2018
DOI: 10.3389/fimmu.2018.01737
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Protective Vaccine Against Lipopolysaccharide-Heterologous Pseudomonas aeruginosa Strains Based on Expression Profiling of Outer Membrane Proteins During Infection

Abstract: Pseudomonas aeruginosa is a ubiquitous opportunistic pathogen, which causes infectious disease in patients with cystic fibrosis and compromised immunity. P. aeruginosa is difficult to eradicate because of its intrinsic resistance to most traditional antibiotics as well as acquired resistance mechanisms after decades of antibiotic usage. A full understanding of the P. aeruginosa pathogenesis mechanisms is necessary for the development of novel prevention and treatment strategies. To identify novel vaccine candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…P. aeruginosa uses FpvA to bind the high-affinity siderophore pyoverdine to capture iron from the host environment and translocate it to the cell cytoplasm through a TonB-dependent system (15). Studies from Wu et al and Liu et al have previously identified and tested FpvA as a potential antigen against P. aeruginosa (16, 17). FpvA displays numerous characteristics often associated with protective antigens: (1) FpvA is present on the surface of the bacterium (18), (2) is expressed during infection (10, 17, 19), (3) is important for bacterial homeostasis and virulence (12, 17, 20, 21), and (4) is present in the majority of P. aeruginosa strains including isolates from CF patients (22, 23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. aeruginosa uses FpvA to bind the high-affinity siderophore pyoverdine to capture iron from the host environment and translocate it to the cell cytoplasm through a TonB-dependent system (15). Studies from Wu et al and Liu et al have previously identified and tested FpvA as a potential antigen against P. aeruginosa (16, 17). FpvA displays numerous characteristics often associated with protective antigens: (1) FpvA is present on the surface of the bacterium (18), (2) is expressed during infection (10, 17, 19), (3) is important for bacterial homeostasis and virulence (12, 17, 20, 21), and (4) is present in the majority of P. aeruginosa strains including isolates from CF patients (22, 23).…”
Section: Introductionmentioning
confidence: 99%
“…Studies from Wu et al and Liu et al have previously identified and tested FpvA as a potential antigen against P. aeruginosa (16, 17). FpvA displays numerous characteristics often associated with protective antigens: (1) FpvA is present on the surface of the bacterium (18), (2) is expressed during infection (10, 17, 19), (3) is important for bacterial homeostasis and virulence (12, 17, 20, 21), and (4) is present in the majority of P. aeruginosa strains including isolates from CF patients (22, 23). In addition, iron acquisition receptor-based vaccines are protective against E. coli, Klebsiella spp., Salmonella enterica serovar Enteritidis, Neisseria gonorrhoeae, Neisseria meningitidis, Staphylococcus aureus , and Haemophilus parasuis in different animal models (2431).…”
Section: Introductionmentioning
confidence: 99%
“…Phagocytosis and intracellular survival assays. The macrophage phagocytosis assay was conducted as described previously, with minor modifications (67). Briefly, 2 ϫ 10 5 iBMDMs were seeded into each well of a 24-well plate 24 h before infection.…”
mentioning
confidence: 99%
“…Next, 10 l of the bacterial suspension was inoculated into each nostril of the mouse, resulting in 1 ϫ 10 7 CFU per mouse. At 3 h postinfection, the BALF was collected as described previously (67). Cells in the BALF from each mouse were collected by centrifugation, resuspended in 500 l 1ϫ red blood cell (RBC) lysis buffer (0.84% NH 4 Cl) for 2 min at room temperature, and then washed once with flow cytometry (FCM) buffer (2% bovine serum albumin [BSA] and 0.5 mM EDTA in PBS [pH 7.4]).…”
mentioning
confidence: 99%
“…OprH was one of the most highly expressed proteins during infection. In addition, OprH is known to be highly immunogenic and accessible by host proteins 79…”
Section: Outer Membrane Proteinsmentioning
confidence: 99%